Attitudes of a sample of students of college of administration and economic toward value of capital and its relationship with some variables - Mohammad, Nasraddin (Humanities Journal of University of Zakho, 2021)
The aim of study is to testify the statistical hypotheses concerning the significant differences between attitudes of a sample of students of college of administration and economic in Zakho University toward value of capital according to the variables of the study. The sample of the research consists of (122) students, which have been selected randomly from population (%74). The researcher used a prepared questionnaire by (Zeydan, 2008) include of (30) items. The results of the research showed that members of research’s sample have very high significant meaningful negative attitudes toward value of capital; also statistical significant differences among them according to the variable of gender, but there are no statistical significant differences among them according to the other variables of the study.